The Impact of the Fall of Constantinople - Kamil, Muhammad Aqil; Kirani, Chintya (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
This research article examines the fall of Constantinople to the Ottoman dynasty in 1453 AD which marked the end of the Byzantine Empire which was then led by Constantinople IX Palaiologos Dragas and became the beginning of the Ottoman Dynasty’s rule in the Mediterranean peninsula. This study analyzes the impacts of the fall of Constantinople in several aspects. The research method in this study uses a qualitative method, namely by reading contemporary history books, historical chronicles, and relevant historical journal and by taking a historical approach. The theoretical framework in this discussion uses the theory  of a historian named Steven Runciman. By using Steven Runciman’s perspective on the discussion of “The Fall of Constantinople in the Hands of the Ottoman Dynasty”, this study aims to provide a detailed understanding of the event and its short-term and long-term impacts on the development of world history. The fundamental and crucial implications of this study state that the turmoil of political, social, economic and cultural dynamics experienced significant changes, scholars in particular provided an intake of ancient Greek literacy that was carried away after the conquest of European society, so that educated people who initially constrained by the backwardness of logical knowledge by religious doctrine educated and became a turning point in the evolution of civilization. So that they are very advanced and dominate in other aspects such as politics, economics, and the military in the future which also have an impact on crucial tragedies in several corner of the world such as colonization, the great revolution of several European countries, and the practice of ideology that spread.